Ion Channel Mimetic Chronopotentiometric Polymeric Membrane Ion Sensor for Surface-Confined Protein Detection - Xu, Y.; Bakker, Eric (American Chemical Society, 2009)
The operation of ion channel sensors is mimicked with functionalized polymeric membrane electrodes, using a surface confined affinity reaction to impede the electrochemically imposed ion transfer kinetics of a marker ion. A membrane surface biotinylated by covalent attachment to the polymeric backbone is used here to bind to the protein avidin as a model system. The results indicate that the protein accumulates on the ion-selective membrane surface, partially blocking the current-induced ion transfer across the membrane/aqueous sample interface, and subsequently decreases the potential jump in the so-called super-Nernstian step that is characteristic of a surface depletion of the marker ion. The findings suggest that such a potential drop could be utilized to measure the concentration of protein in the sample. Because the sensitivity of protein sensing is dependent on the effective blocking of the active surface area, it can be improved with a hydrophilic nanopore membrane applied on top of the biotinylated ion-selective membrane surface. On the basis of cyclic voltammetry characterization, the nanoporous membrane electrodes can indeed be understood as a recessed nanoelectrode array. The results show that the measuring range for protein sensing on nanopore electrodes is shifted to lower concentrations by more than 1 order of magnitude, which is explained with the reduction of surface area by the nanopore membrane and the related more effective hemispherical diffusion pattern.